2017
DOI: 10.1007/s00268-017-3989-4
|View full text |Cite
|
Sign up to set email alerts
|

Early Hepatic Artery Thrombosis After Liver Transplantation: What is the Impact of the Arterial Reconstruction Type?

Abstract: The type of arterial reconstruction used for arterial anastomosis during primary liver transplantation has an impact on the occurrence of early HAT. The use of a long graft artery is an independent risk factor of early HAT. Thereby, we recommend the use of a short graft artery with a direct path when feasible to reduce the occurrence of early HAT after primary liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 35 publications
2
41
0
4
Order By: Relevance
“…All of the transplants were performed over a relatively short time span (7 years) by a single team, using all of the same standardized operative strategies and techniques, as well as by employing those stated protocols for both perioperative management and immunosuppression. Interestingly, the surgical approaches that were applied for these patients were a combination of what have been recommended by different teams over the last decade, for instance, the use of microsurgical techniques, PV hypoplasia corrections, reducing the use of arterial vascular grafts, multiple USD checks during and after the LTs, and an early diagnosis and a rapid aggressive management for any vascular problem, among others . With a zero incidence of graft loss related to vascular problems and with only two of the 122 currently functioning grafts having a non‐clinically relevant vascular sequela, it can be concluded that the strategy was instrumental in achieving the excellent outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All of the transplants were performed over a relatively short time span (7 years) by a single team, using all of the same standardized operative strategies and techniques, as well as by employing those stated protocols for both perioperative management and immunosuppression. Interestingly, the surgical approaches that were applied for these patients were a combination of what have been recommended by different teams over the last decade, for instance, the use of microsurgical techniques, PV hypoplasia corrections, reducing the use of arterial vascular grafts, multiple USD checks during and after the LTs, and an early diagnosis and a rapid aggressive management for any vascular problem, among others . With a zero incidence of graft loss related to vascular problems and with only two of the 122 currently functioning grafts having a non‐clinically relevant vascular sequela, it can be concluded that the strategy was instrumental in achieving the excellent outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…As per the protocol, all of the patients had received the same induction (anti‐interleukin‐2 monoclonal antibodies) and maintenance immunosuppression therapy (intent for tacrolimus monotherapy—associated with steroids and/or mycophenolate mofetil, when required by their clinical needs). In addition, as per the protocol, all of the patients were followed perioperatively by implementing a multifaceted strategy aimed at reducing the incidence of vascular complications; this latter strategy was used during the whole period of the study and it consisted of 4 main complementary aspects:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…No adequate arterial flow was based on surgeon 0 s judgment and/or in the case of flow lower than 100 ml/min measured by intraoperative transit-time ultrasound. Alternative approaches to arterialize the graft are needed in these cases [2,19,20], with aortohepatic conduits being the most commonly reported option [19,20]. We excluded patients with arterial conduits from our study.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have evaluated the results of using aortohepatic conduits [19]. In most of these studies, the use of arterial conduits has been demonstrated to be and independent risk factor for both early and late HAT as well as for biliary complications [19,20]. Indeed, some studies have shown lower patient and graft survival rates when using arterial conduits [7,21], leading authors, such as Hibi et al [7], to recommend strictly limiting their use.…”
Section: Discussionmentioning
confidence: 99%